(3GdQjGVjGJ aj GdYdhe GdeGdjI hGdEOGQjI (B/s - (3TGgQ, KGFQ ajUds; (3YchQ, SGeQ eMeO s ((3YeGf(B: s (3OGQ GdMGeO(B, s, 2008)
(3eaGgje QjGVjI CSGSjI dHfGA GdfehPL GdQjGVj, eaghe GdOGdI hGdOGdI GdNWjI (B-(3GdefXheI GdNWjI hGdJhGRf aj GdShb, GdeYGOdGJ hGdOhGd GdJQHjYjI, GdeYGOdGJ hGdOhGd GdCSjI hGddhZGQjJejI hJWHjbGJgG GdEbJUGOjI, GdQjGVjGJ aj GdYdhe GdeGdjI, GdJaGVd hJWHjbGJg GdEbJUGOjI, GdJaGVd GdLRFj, GdeUahaGJ hJWHjbGJgG GdEbJUGOjIs
((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdGOGQIs; (3GdJaGVd hGdJcGeds; (3GdQjGVjGJs; (3GdeUahbGJs